Sicad: Smart Information System For Village Administration As An Empowering Ngadiluwih Village Kediri In Improving Community Services - Astuti, Ani Budi; Nugroho, Waego Hadi; Sumarminingsih, Eni; Rotchildi, Gusti Ayu Putu Rawi; Sa'diyah, Nur Kamilah; Kalangi, Olyvia Maria; Ibnu, Muhammad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2023)
The Ngadiluwih Village Government, Kediri Regency, East Java Province also really needs an Android-based application so that the reach of access is wide in an effort to digitize villages to improve village administration services online. The purpose of this community service activity is to build and develop the Ngadiluwih Village Government Smart Information System application, which is abbreviated as Ngadiluwih SICAD in the context of empowering Ngadiluwih Village in an effort to improve online village administration services to the community. The socialization, implementation, and assistance were also carried out to village officials and the community regarding the Ngadiluwih SICAD application product. The results of this activity show that the Ngadiluwih SICAD that has been built is in accordance with the expectations and needs of Ngadiluwih Village and the community with 14 types of letter facilities.